OnabotulinumtoxinA Reduces Health Resource Utilization in Chronic Migraine: PREDICT Study. (25th May 2023) - Becker, Werner J.; Boudreau, Guy; Finkelstein, Ian; Graboski, Corrie; Ong, May; Christie, Suzanne; Sommer, Katherine; Bhogal, Meetu; Davidovic, Goran
ABSTRACT: Background: PREDICT was a Canadian, multicenter, prospective, observational study in adults naïve to onabotulinumtoxinA treatment for chronic migraine (CM). We descriptively assess health resource utilization, work productivity, and acute medication use. Methods: OnabotulinumtoxinA (155–195 U) was administered every 12 weeks over 2 years (≤7 treatment cycles). Participants completed a 4-item health resource utilization questionnaire and 6-item Work Productivity and Activity Impairment Questionnaire: Specific Health Problem V2.0. Acute medication use was recorded in daily headache diaries. Treatment-emergent adverse events were recorded throughout the study. Results: A total of 197 participants were enrolled, and 184 received ≥1 treatment with onabotulinumtoxinA and were included in the analysis. Between baseline and the final visit, there were decreases in the percentage of participants who reported headache-related healthcare professional visit(s) (96.2% to 76.8%) and those who received headache-related diagnostic testing (37.5% to 9.9%). Reductions from baseline were also observed in the mean number of headache-related visits to an emergency room/urgent care clinic (2.5 to 1.4) and median headache-related hospital admissions (4.0 to 1.0). OnabotulinumtoxinA improved work productivity and reduced the mean (standard deviation) number of hours missed from work over a 7-day period (6.1 [9.7] to 3.0 [6.8]). Mean (standard deviation) acute medication use decreased from baseline (15.2 [7.6] to 9.1 [6.5] days). No new safety signals were identified. Conclusions: Real-world evidence from PREDICT demonstrates that onabotulinumtoxinA treatment for CM in the Canadian population reduces health resource utilization and acute medication use and improves workplace productivity, supporting the long-term benefits of using onabotulinumtoxinA for CM.